Development and Characterization of Atorvastatin Calcium Sustained Release Tablet Using Carbomer-974 and Hypromellose-15000 cps - Akbar, S.; Bhatta, R.; Rahman, M. A.; Hossain, M. S.; Bhuiyan, M. S.; Uddin, M. G. (Journal of Scientific Research, 2017)
A new sustained release formulation of Atorvastatin Calcium tablet, exhibiting improved swelling property and compatibility to prolong the drug release was prepared. Sustained release tablets were formulated using varying concentration of Carbomer-974 and Hypromellose-15000 cps, by direct compression method. Physical characteristics, compactibility, swelling index and drug content uniformity of the prepared formulations were determined. The drug release studies was carried out in USP dissolution test apparatus II (paddle) using phosphate buffer of pH 6.8 as dissolution medium for 8 hours and documented the effects of polymers on the drug release profile. The release mechanism was explored and explained with Zero order & Higuchi kinetic models. Formulation F1 and F5 were best fitted in the Higuchi model, representing diffusion mechanism of drug release, while Formulations F2, F3 and F4 showed Zero order model of drug release profile. The drug release pattern, compactibility and swelling index property of the formulated preparations were concentration dependent of the polymers used. Further study is necessary to evaluate the in vitro-in vivo relationship, but this study will be helpful for future to exploit the potential of this drug delivery system for the benefit of the mankind.